1974
DOI: 10.1073/pnas.71.3.932
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Antibody-Induced Topographical Redistribution of Surface Immunoglobulins, Alloantigens, and Concanavalin A Receptors on Mouse Lymphoid Cells

Abstract: Redistribution of surface immunoglobulins, H-2b, Thy-1.2, and TL.1,2,3 alloantigens, and concanavalin A receptors on mouse lymphoid cells induced by hybrid rabbit F(ab')2 antibody (anti-mouse immunoglobulin/anti-visual marker or anti-concanavalin A/anti-visual marker) was studied by immunofluorescence. When used directly to label surface immunoglobulin, and indirectly to label alloantigens and concanavalin A receptors, hybrid antibodies induced similar displacement of all surface components from a uniform dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…We hypothesized that AMPA receptors on the cell surface at the time of brain slice preparation do react fully with BS 3 or biotin, but cross‐linked product continues to accumulate because new receptors are still being delivered to the surface, where they replenish the pool available for cross‐linking or biotinylation. Supporting this, it has long been known that membrane trafficking slows but does not stop at 4°C (Stackpole et al, ), and we have observed constitutive insertion of new AMPA receptors onto the surface of cultured nucleus accumbens neurons at 4°C (Mangiavacchi and Wolf, ).…”
Section: Commentarysupporting
confidence: 75%
“…We hypothesized that AMPA receptors on the cell surface at the time of brain slice preparation do react fully with BS 3 or biotin, but cross‐linked product continues to accumulate because new receptors are still being delivered to the surface, where they replenish the pool available for cross‐linking or biotinylation. Supporting this, it has long been known that membrane trafficking slows but does not stop at 4°C (Stackpole et al, ), and we have observed constitutive insertion of new AMPA receptors onto the surface of cultured nucleus accumbens neurons at 4°C (Mangiavacchi and Wolf, ).…”
Section: Commentarysupporting
confidence: 75%
“…For example, binding and aggregation of label could stimulate endocytosis and membrane turnover, although de Petris and Raft (15) have shown that these activities in themselves are not adequate BROWN ASD REVEL Reversibility of Cell Surface Label Rearrangement to explain the observed rearrangement. It has been proposed that an intracellular network might be responsible for rearranging surface molecules (15,35,50). Binding and aggregation of label could cause and maintain the interaction of the binding sites with this network.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the first component, clustering, results from crosslinking of surface sites by multivalent label molecules, since univalent antibody fragments appear uniformly distributed on the cell surface (16,35,53). Stackpole et al (50), however, have demonstrated that clustering can occur even with strictly univalent reagents. They suggest that interaction of label with its binding sites may cause an alteration which thermodynamically favors aggregation.…”
mentioning
confidence: 99%
“…If so, it might be possible to follow the morphogenesis of the virus envelope by directly visualizing the dynamic movement and distribution of these projections on the surfaces of virus-infected cells. This would eliminate the need for externally applied ligands, which are generally required to identify a specific molecule but which unavoidably perturb the native configuration of the labeled molecules (4,6,32).…”
mentioning
confidence: 99%